DNA bar-coding reveals source and patterns of Thaumastocoris peregrinus invasions in South Africa and South America - Nadel, R. L.; Slippers, B.; Scholes, M. C.; Lawson, S. A.; Noack, A. E.; Wilcken, Carlos Frederico [UNESP]; Bouvet, J. P.; Wingfield, M. J. (Springer, 2010)
Thaumastocoris peregrinus is a recently introduced invertebrate pest of non-native Eucalyptus plantations in the Southern Hemisphere. It was first reported from South Africa in 2003 and in Argentina in 2005. Since then, populations have grown explosively and it has attained an almost ubiquitous distribution over several regions in South Africa on 26 Eucalyptus species. Here we address three key questions regarding this invasion, namely whether only one species has been introduced, whether there were single or multiple introductions into South Africa and South America and what the source of the introduction might have been. To answer these questions, bar-coding using mitochondrial DNA (COI) sequence diversity was used to characterise the populations of this insect from Australia, Argentina, Brazil, South Africa and Uruguay. Analyses revealed three cryptic species in Australia, of which only T. peregrinus is represented in South Africa and South America. Thaumastocoris peregrinus populations contained eight haplotypes, with a pairwise nucleotide distance of 0.2-0.9% from seventeen locations in Australia. Three of these haplotypes are shared with populations in South America and South Africa, but the latter regions do not share haplotypes. These data, together with the current distribution of the haplotypes and the known direction of original spread in these regions, suggest that at least three distinct introductions of the insect occurred in South Africa and South America before 2005. The two most common haplotypes in Sydney, one of which was also found in Brisbane, are shared with the non-native regions. Sydney populations of T. peregrinus, which have regularly reached outbreak levels in recent years, might thus have served as source of these three distinct introductions into other regions of the Southern Hemisphere.
Keywords: COI diversity; Eucalyptus plantation forestry; Invasive insect pest; Thaumastocoridae; Hemiptera